Engineering General Intelligence, Part 1 A Path to Advanced AGI via Embodied Learning and Cognitive Synergy - Goertzel, Ben; Pennachin, Cassio; Geisweiller, Nil (Atlantis Thinking Machines, 2014)
The work outlines a novel conceptual and theoretical framework for understanding Artificial General Intelligence and based on this framework outlines a practical roadmap for the development of AGI with capability at the human level and ultimately beyond.